1D.01: BLOOD PRESSURE CONTROL AFTER PEDIATRIC KIDNEY TRANSPLANTATION. (June 2015) - Stabouli, S.; Printza, N.; Dotis, J.; Gogka, C.; Kollios, K.; Kotsis, V.; Papachristou, F.
Abstract : Objective: To assess the prevalence of hypertension and blood pressure (BP) control over years after pediatric kidney transplantation. Design and method: We reviewed the medical charts of consecutive kidney transplants performed in 71 children and adolescents (age range 2–18 years) between 1990–2012. BP index was used as a measure of the severity of BP elevation. Hypertension was defined as systolic and/or diastolic BP greater than the 95th percentile for age and sex, or as being on antihypertensive medication. Results: Blood pressure levels as expressed by BP index presented gradual decrease after Tn. BP indexes at 5, and 10 years post Tn were significantly lower than BP indexes before Tn (SBP index = 1.038 before vs. SBP index = 0.881 at 5 years, P = 0.001, and SBP index = 1.038 before vs. SBP index = 0.871 at 10 years, P = 0.001, DBP index = 0.982 before vs. DBP index = 0.895 at 5 years, P < 0.05, and DBP index = 0.982 before vs. DBP index = 0.890 at 10 years, P < 0.05). The number of patients who were receiving antihypertensive treatment increased after Tn (44.7 % before Tn, 69.7% at 12 months, 66% at 5 years and 53.8% at 10 years post Tn). There was an increased likelihood of receiving antihypertensive treatment at 5 and 10 years post Tn, if a patient was under treatment before Tn (5 years OR 3.778, 95% CI 1.308–10.915, P = 0.001, 10 years OR 4.500, 95% CI 1.218–16.622, P < 0.005). The prevalence of hypertension by office BP presented a decreasing trend after Tn (Figure). BP control by antihypertensive treatment was 16.7% before Tn, 41.3% at 12 months, 66.7% at 5 years, and 44.4% at 10 years post Tn and was achieved with a lower number of drugs compared to the number of antihypertensive drugs before Tn (Figure). Figure. No caption available. Conclusions: Hypertension remains a frequent complication in pediatric kidney recipients even years after kidney Tn, but the severity of BP evaluation may present a significant decrease. BP control seems to peak at 5 years post Tn and can be achieved with fewer drugs with increasing time after Tn.